FACTORS AND CRITERIA OF BICYCLE FACILITIES TO ENCOURAGE CYCLING TO WORK - Asma Rosyidah; Hanson Endra Kusuma (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Cycling to work is one kind of bicycle commuting activity that has many benefits. This study was conducted to identify the factors that influence the motivation of cycling to work. The encouraging and discouraging factors for cycling need to be known as considerations for determining strategies that can increase the number of cyclists. Criteria for bicycle facilities in the workplace that are considered important by users are also identified. Data were collected through an online questionnaire with a mixed-method approach. Data were analyzed using factor analysis (FA). The results of factor analysis (FA) is there are 4 dimensions of the driving factors for cycling to work, including ‘environment and self’, ‘availability of facilities’, ‘accessibility’, and ‘social and hobbies’. Meanwhile, the dimensions of the deterrent factors are three, including ‘road conditions’, ‘unavailability of facilities’, and ‘accessibility and personal reasons’. The criteria for bicycle facilities in the workplace are two dimensions, including ‘convenience and security’ and ‘completeness of facilities’. From the mean value, ‘convenience and security’ is considered more important than ‘completeness of facilities’.